2000
DOI: 10.1007/bf02296147
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of order-statistics models for ranking data

Abstract: data augmentation, Gibbs sampling, order-statistics model, ranking data,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Others have proposed fullinformation maximum likelihood methods using Monte Carlo expectation-maximization algorithms (Poon & Lu, 2009;Xu, Poon, & Lee, 2008). Yao and Böckenholt (1999) and Yu (2000) showed that Bayesian Thurstonian ranking models are amenable to Markov chain Monte Carlo (MCMC) algorithms by using data augmentation with Gibbs sampling (Gelfand & Smith, 1990;Tanner & Wong, 1987). Using this approach, the unobserved differences are specified as missing data in a complete-data likelihood function to create the Bayesian probability model:…”
Section: Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have proposed fullinformation maximum likelihood methods using Monte Carlo expectation-maximization algorithms (Poon & Lu, 2009;Xu, Poon, & Lee, 2008). Yao and Böckenholt (1999) and Yu (2000) showed that Bayesian Thurstonian ranking models are amenable to Markov chain Monte Carlo (MCMC) algorithms by using data augmentation with Gibbs sampling (Gelfand & Smith, 1990;Tanner & Wong, 1987). Using this approach, the unobserved differences are specified as missing data in a complete-data likelihood function to create the Bayesian probability model:…”
Section: Estimation Methodsmentioning
confidence: 99%
“…The mean and variance are often specified as being constant over observations, although some researchers have discussed letting the mean μ i vary over observations, due to its dependence on covariates (e.g., Yu, 2000). This is not a major extension of the model, but it is worth discussion since, in practice, covariates are common and there are some important considerations in terms of how their effects are specified and identified.…”
Section: Including Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The issues of leniency and central tendency are well known in psychology: it is often observed that individuals have a tendency to place objects in the middle of the scale and to avoid extreme positions. Similar problems have also been studied by Poon and Chan (2002), Fligner and Verducci (1990), and Yu (2000). The mathematics of these methods has been described by Alvo and Yu (2014), Marden (1995), andCritchlow et al (1991).…”
Section: Introductionmentioning
confidence: 91%
“…Models based on orderstatistics are discussed in Thurstone (1927), Yellot (1977), Critchlow (1980), Daniels (1950), Mosteller (1951) and Yu (2000). Order-statistics based models consider a latent utility y i , of ith item, i = 1, .…”
Section: Introductionmentioning
confidence: 99%